Obesity/Metabolic Syndrome and Diabetes Mellitus on Peri-implantitis - de Oliveira, Paula Gabriela Faciola Pessôa; Bonfante, Estevam A.; Bergamo, Edmara T.P.; de Souza, Sérgio Luis Scombatti; Riella, Leonardo; Torroni, Andrea; Benalcazar Jalkh, Ernesto B.; Witek, Lukasz; Lopez, Christopher D.; Zambuzzi, Willian Fernando [UNESP]; Coelho, Paulo G. (Elsevier, 2020)
Literature has reported that up to 50% of dental implants may be affected by peri-implantitis, a bacteria-induced chronic inflammatory process, which promotes osteoclast-mediated bone resorption and inhibits bone formation, leading to progressive bone loss around implants. Current evidence points toward an increased risk for the development of peri-implantitis in both obesity/metabolic syndrome (MetS) and diabetes mellitus (DM) conditions relative to the healthy population. Currently, there is no effective treatment for peri-implantitis and the 50% prevalence in MetS and DM, along with its predicted increase in the worldwide population, presents a major concern in implant dentistry as hyperglycemic conditions are associated with bone-healing impairment; this may be through dysfunction of osteocalcin-induced glucose metabolism. The MetS/DM proinflammatory systemic condition and altered immune/microbiome response affect both catabolic and anabolic events of bone-healing that include increased osteoclastogenesis and compromised osteoblast activity, which could be explained by the dysfunction of insulin receptor that led to activation of signals related with osteoblast differentiation. Furthermore, chronic hyperglycemia along with associated micro- and macro-vascular ailments leads to delayed/impaired wound healing due to activation of pathways that are particularly important in initiating events linked to inflammation, oxidative stress, and cell apoptosis; this may be through deactivation of AKT/PKB protein, which possesses a pivotal role in drive survival and eNOS signaling. This review presents an overview of the local and systemic mechanisms synergistically affecting bone-healing impairment in MetS/DM individuals, as well as a rationale for hierarchical animal model selection, in an effort to characterize peri-implantitis disease and treatment.
Keywords: bone loss; dental implants; inflammation; obesity; osseointegration